Pharmacokinetics of naftopidil, a novel anti-hypertensive drug, in patients with hepatic dysfunction. Issue 823 (May 1994) - Farthing, M. J.; Alstead, E. M.; Abrams, S. M.; Haug, G.; Johnston, A.; Hermann, R.; Niebch, G.; Ruus, P.; Molz, K. H.; Turner, P.
Abstract : The pharmacokinetics of naftopidil, a novel alpha-1 adrenoceptor-blocking antihypertensive, were investigated in ten patients (9M/1F) with hepatic dysfunction after oral administration (50 mg, tablet) and after an intravenous infusion of 5.0 mg over 2 minutes. Results were compared to a control group of 12 healthy subjects (6M/6F) of a previous investigation, which was carried out according to the identical study protocol. The pharmacokinetic parameters obtained for the i.v. administration were comparable in both groups (half life 3.6 +/- 3.4 hours in liver-impaired subjects versus 3.3 +/- 2.1 hours in controls; clearance 11.9 +/- 4.7 ml/minute/kg versus 11.0 +/- 1.6 ml/minute/kg). Following oral administration the plasma levels and half-life times of naftopidil were significantly increased in liver impairment (t1/2 16.6 +/- 19.3 hours versus 5.4 +/- 3.2 hours in controls; P = 0.012). Mean values for the absolute bioavailability in patients with hepatic dysfunction were significantly higher (mean 75%, median 53%, range 13.4-211.0%) compared to healthy subjects (mean 17%, median 16%, range 6.7-29.6%, P = 0.001). Reduction of functional hepatic blood flow in chronic liver disease or, as evidenced in one case as a consequence of shunt surgery, is the probable cause of the observed alteration in naftopidil kinetics. This phenomenon occurred only following the oral 50 mg dose whereas the intravenous 5 mg dose obviously still could be normally handled. Naftopidil demethylation and hydroxylation were both less and non-uniformly affected. The pharmacokinetic findings suggest that in patients with severe hepatic impairment or evidence for marked changes in hepatic blood flow the dose of naftopidil may require adjustment to the lower end of the therapeutic range and/or may be limited to once daily. However, before definite conclusions can be drawn, further steady-state studies are required. Despite the pharmacokinetic discrepancies no difference in drug tolerability was seen between patients and healthy subjects.